Determinants of Educational Outcomes in Yaroslavl, Russia - Edgar Demetrio Tovar-García (Universidad Autónoma de Baja California, 2013)
This paper examines the determinants of educational outcomes in Yaroslavl, Russia. Previous findings for this country point out that parents' educational level and income are the main explanatory variables. To investigate these factors, in 2009 we applied a questionnaire to a random sample of two thousand ninth grade students from 65 schools. We performed a regression analysis with ordinary lest squares and Newey-West robust standard errors and probit analysis. We found that the most common explanatory variables, family resources (including cultural capital, social capital and socioeconomic status), have a small but statistically significant positive effect on educational achievements and trajectories.